2014
DOI: 10.1002/em.21851
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the lung methylome in allergic airway hyper‐responsiveness

Abstract: Asthma is a chronic airway disorder characterized by recurrent attacks of breathlessness and wheezing, affecting 300 million people around the world (available at: www.who.int). To date, genetic factors associated with asthma susceptibility have been unable to explain the full etiology of asthma. Recent studies have demonstrated that the epigenetic disruption of gene expression plays an equally important role in the development of asthma through interaction with our environment. We sensitized 6-week-old C57BL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…However, how the persistent epigenetic alteration of PDE4D is established in asthmatic ASMCs remains unknown. We previously demonstrated the changes in mRNA level of the DNA methylation modulators, including Dnmt3A, methyl-CpG-binding domain proteins (Mbd2 and Mbd3), and ten-eleven translocation proteins (Tet1) in mouse chronically exposed to house allergen (26). It will be informative to further examine how PDE4D is epigenetically regulated by these DNA methylation modulators, and how these modifications persist in the presence or absence of stimuli as in our cultured asthmatic ASMCs.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, how the persistent epigenetic alteration of PDE4D is established in asthmatic ASMCs remains unknown. We previously demonstrated the changes in mRNA level of the DNA methylation modulators, including Dnmt3A, methyl-CpG-binding domain proteins (Mbd2 and Mbd3), and ten-eleven translocation proteins (Tet1) in mouse chronically exposed to house allergen (26). It will be informative to further examine how PDE4D is epigenetically regulated by these DNA methylation modulators, and how these modifications persist in the presence or absence of stimuli as in our cultured asthmatic ASMCs.…”
Section: Discussionmentioning
confidence: 83%
“…DNA methylation changes are associated with asthma (19,20) and linked to specific triggers of asthma, such as pollutant exposures (21-24). We previously reported that acute exposure to house dust mite (HDM) induced AHR in a mouse model, and the AHR induction was associated with epigenetic modulations of genes related to ASMC proliferation and contraction (25,26). Specifically, we found promoter demethylation of phosphodiesterase 4D (Pde4d) gene in tracheal ASMCs isolated from HDM-exposed mice.…”
mentioning
confidence: 92%
“…Differences in DNA methylation might be intrinsic to asthma phenotypes, but they also might have been induced by allergen exposure. The latter possibility is supported by results from mouse models of asthma showing dynamic changes in DNA methylation from allergen challenge (Cheng et al, 2014; Shang et al, 2013). In support of allergen-induced changes in DNA methylation, ovalbumin sensitization of mice decreased DNA methyltransferase 1 (DNMT1) mRNA abundance which correlated with increased methylation of the DNMT1 gene (Verma et al, 2013).…”
Section: Epigenetic Control Of Gene Expression In Lung Tissue Remomentioning
confidence: 78%
“…Moreover, adoptive transfer of these DCs from pups of allergic mothers into offspring from nonatopic mothers transferred increased susceptibility to allergic disease to recipients despite there being no differences in DNA sequences. Although the specific genes conferring susceptibility in this study were not identified, more recent studies have shown that alterations in the lung methylome particularly in genes involved in the TGFB2 signaling pathway are associated with alterations in airway smooth muscle remodeling and the subsequent development of AHR (Cheng et al, 2014). As the study of the methylome in asthma is in its infancy, there will undoubtedly be more knowledge to be gained in this area.…”
Section: Other Factors Regulating the Asthma Phenotypementioning
confidence: 96%